Improvement of evolutionary algorithm based on schema exploiter - Maruyama, Takashi; Kita, Eisuke (Computer Assisted Methods in Engineering and Science, 2022)
Stochastic Schemata Exploiter (SSE) is one of the evolutionary optimization algorithms for solving the combinatorial optimization problems. We present the Extended SSE (ESSE) algorithm which is composed of the original SSE and new ESSE operations. The ESSE is compared with the original SSE, simple genetic algorithm (SGA), and GA with Minimal Generation Gap (MGG) in some test problems in order to discuss its features.